Friday on My Mind: Re-Assessing the Impact of Protest Size on Government Concessions. (August 2022) - Butcher, Charles; Pinckney, Jonathan
Do more protesters on the streets make governments likely to grant their demands? Several studies link protest size and government concessions. Yet existing research has limitations: many studies suffer from potential endogeneity due to potential protesters joining protests when they anticipate that concessions are likely, causal mechanisms are often unclear, and many of the most rigorous event-level studies are limited to Western democracies. We reexamine this relationship in a non-Western sample using a novel instrumental variable approach, using Fridays as an instrument for exogenous variation in protest size in predominately Muslim countries. We perform two analyses: one using the NAVCO 3.0 dataset, and the second using the Mass Mobilization in Autocracies Dataset (MMAD). In both analyses exogenous variation in protest size negatively affects the likelihood of concessions. Larger protests are less likely to receive government concessions. We suggest these surprising results point to the importance of unanticipated protests that produce new information about regime stability to motivate government concessions.